Protective factors for early initiation of breastfeeding among Brazilian nursing mothers - Lemos, Giovana Gaglianone; Sousa, Taciana Maia de; Souza, Rafaela Cristina Vieira e; Ferreira, Larissa Bueno; Miranda, Cristianny; Santos, Luana Caroline dos (Frontiers in Pediatrics, 2023)
Objectives: Evaluate the protective factors associated with early initiation of breastfeeding. Methods: Cross-sectional study conducted with Brazilian nursing mothers. Breastfeeding in the first hour of life and difficulty initiating breastfeeding in the birth room were adopted as outcome variables and associated with other maternal and child information. Poisson regression was conducted to synthesize the data. Results: Among 104 nursing mothers evaluated, 56.7% reported breastfeeding in the first hour of life and 43% had difficulty initiating breastfeeding in the birth room. There was a higher prevalence of breastfeeding in the first hour of life among mothers with previous breastfeeding experience (PR=1.47, 95% CI 1.04-2.07). Difficulty initiating breastfeeding in the birth room was more prevalent among mothers who did not receive breastfeeding guidance during antenatal care (PR=2.83, 95% CI 1.43-4.32) and those without previous breastfeeding experience (PR=2.49, 95% CI 1.24-6.45). Conclusion: These findings highlight the importance of adequate professional guidance, especially for primiparous mothers.